The Role of Indonesian NGOs in Palestine Advocacy: From Humanitarian Aid to Policy Campaigns (Palestine Issues on Indonesian Society, 2025)
This paper investigates the evolution of Indonesian non-governmental organizations (NGOs) in their advocacy for Palestine, shifting from humanitarian aid initiatives to more politically engaged policy campaigns. The study analyzes the activities of key Indonesian NGOs, including those focused on human rights, social justice, and Islamic charity, in their efforts to address the humanitarian needs of Palestinians while also engaging with global political discussions surrounding the Israeli-Palestinian conflict. The research examines how Indonesian NGOs have adapted their approaches over time, transitioning from providing aid during periods of crisis to advocating for Palestinian political rights and supporting international efforts for peace. The paper also explores the role of Indonesian civil society in raising awareness of the Palestinian issue domestically, mobilizing support among the public and influencing government policy. By focusing on the strategies used by Indonesian NGOs, the paper highlights the broader implications for grassroots advocacy in global solidarity movements and the changing nature of international aid and political engagement.